Pulmonary delivery of insulin by dry powder inhaler formulations - Mohsen Imenshahidi; Mona Kabiri; Mohammad Jandaghi; Seyed Salman Razavi Rouhani; Khalil Abnous; Gholamreza Karimi; Mohsen Tafaghodi (Iranian Journal of Basic Medical Sciences)
Objective(s): Insulin therapy is critical in diabetic patients for controlling blood glucose levels. In recent years, pulmonary insulin delivery has emerged as an alternative approach for overcoming the therapeutic disadvantages of subcutaneous insulin administration, such as pain, infection risk, and needle phobia. To develop the pulmonary insulin formulation, five insulin-containing dry powder inhalers (DPIs) with different excipients were tested in diabetic rats.Materials and Methods: Formulations were inoculated endotracheally to diabetic rats induced by streptozotocin. Insulin and glucose assays were performed on blood samples taken from the carotid artery at different intervals, including baseline and 1–4 hr after insulin administration. Results: The results illustrated that five formulations (F1-F5) could gradually increase the plasma insulin level during time points of the study. The first and third formulations comprising insulin, mannitol, and sodium citrate in the absence (F1) or presence of sodium alginate (F3) also declined plasma glucose levels in animals. Conclusion: The results confirmed that the pulmonary formulations could deliver and release insulin molecules in a good manner, and the biological activity of the two formulations, including F1 and F3, is acceptable and comparable to the subcutaneous insulin. Our findings support that the mentioned DPI products could have therapeutic potential as an alternative to subcutaneous insulin. Further investigations are needed to prove the capability of F1 and F3 spray-dried products to treat diabetic individuals.